Kto się boi księcia Metternicha? - Tarnawski, Eduard (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
Th e author proposes a test for the propensity of being a reactionary that he calls ”Metternich test”, although Robert Stewart Castlereagh (1769–1822) could also be called as an examiner. Undoubtedly only Russian tsars can be considered reactionary monarchs, starting from Nicholas I (1796–1855). To judge whether president Putin is a reactionary we need authority of Alexandr Solzhenitsyn (1918–2008). Although Henry Kissinger is called Metternich of 20th century, he is not suit for the function of examiner. Author elaborates on the faith Metternich had in love as a force that makes politics possible. A person that can’t understand the life of other people, cannot understand history. Aft er Nicholas I became tsar all Russian doctinaires, such as Sergey Uvarov (1786–1855), Konstantin Leontiev (1831–1891) and Konstantin Pobedonostsev 1827–1907), formulated principles of reaction. The paper ends with Wacław Nałkowski’s (1851–1911) critique of Henryk Sienkiewicz as a reactionary.